Clever Maids, Fearless Jacks, and a Cat : Fairy Tales from a Living Oral Tradition - Lannon, Alice, 1927-2013; Power, Pius, 1915-1993; Blair, Graham; Greenhill, Pauline; Lovelace, Martin J.; Best, Anita, 1948- (Book collections on Project MUSE., 2018)
"Passed on orally between generations as a community tradition, these sensitive and artful tales don't appear anywhere in print. Features ethnopoetic transcriptions from authors to give authentic accounts of "living" oral performances from the past century and to demonstrate the artistry that is possible without written word"--Provided by publisher